2018
DOI: 10.1016/j.chembiol.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Epidithiodiketopiperazines Inhibit Protein Degradation by Targeting Proteasome Deubiquitinase Rpn11

Abstract: The 26S proteasome is the major proteolytic machine for breaking down cytosolic and nuclear proteins in eukaryotes. Due to the lack of a suitable assay, it is difficult to measure routinely and quantitatively the breakdown of proteins by the 26S proteasome in vitro. In the present study, we developed an assay to monitor proteasome-mediated protein degradation. Using this assay, we discovered that epidithiodiketopiperazine (ETPs) blocked the degradation of our model substrate in vitro. Further characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 41 publications
(65 reference statements)
0
28
0
Order By: Relevance
“…One core component of the lid is a Jab1/MPN domain-associated metalloisopeptidase (JAMM) domain-containing protein Rpn11 (POH1/PSMD14) that couples deubiquitination with degradation ( Figure 1B) [35,36]. The development of Rpn11 inhibitors might have the ability to expand effective UPS inhibitors in the clinic, as discussed below [37][38][39][40]. The base of the 19S RP includes a ring-shaped heterohexamer of AAA+ ATPases that engage and unfold substrate polypeptides to allow for their translocation into the proteolytic pore of the 20S CP [8,16,31].…”
Section: S Proteasomementioning
confidence: 99%
See 1 more Smart Citation
“…One core component of the lid is a Jab1/MPN domain-associated metalloisopeptidase (JAMM) domain-containing protein Rpn11 (POH1/PSMD14) that couples deubiquitination with degradation ( Figure 1B) [35,36]. The development of Rpn11 inhibitors might have the ability to expand effective UPS inhibitors in the clinic, as discussed below [37][38][39][40]. The base of the 19S RP includes a ring-shaped heterohexamer of AAA+ ATPases that engage and unfold substrate polypeptides to allow for their translocation into the proteolytic pore of the 20S CP [8,16,31].…”
Section: S Proteasomementioning
confidence: 99%
“…In addition to capzimin, natural products such as thiolutin and gliotoxin were also identified as active inhibitors of JAMM proteases, including Rpn11. These compounds are active in cell culture and inhibit proteasome function by chelating the zinc ion in the Rpn11 active site [38,39]. However, these compounds are less specific towards Rpn11 than capzimin.…”
Section: Block the Removal Of Ubiquitin Chains From Substrates: Rpn11mentioning
confidence: 99%
“…Previous studies have demonstrated that PSMD14 promotes tumor progression by regulating key anti-cancer proteins such as c-jun, p53, SNAIL, mTOR, and E2F1 [17][18][19][20][21][22]24]. Importantly, small molecule inhibitors targeting PSMD14 were shown to be prospects for potential clinical application [25][26][27][28]. However, the expression of PSMD14 in NSCLC and the underlying mechanism by which PSMD14 is involved in NSCLC development remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence revealed that necrotic cell death induced by GT in murine thymocytes is associated with activation of a redox active calcium channel in the plasma membrane (Hurne et al, 2002). The inhibition of proteasome activity is one of the putative molecular targets of GT-mediated apoptosis in immune cells (Kroll et al, 1999;Dolan et al, 2015;Li et al, 2018). Based on the fact that the disulfide bridge of GT allows the cross linking with proteins and generates reactive oxygen species (ROS) through the redox cycling between reduced and oxidized forms, ROS is believed to be also responsible for DNA damage and apoptosis in cells of immune system (Harms et al, 2015;Nouri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%